What determines the financial decision-making: reason or emotion? - Santos, José Odálio dos; Barros, Carlos Augusto Silva (Review of Business Management, 2011)
It is important to detach that nor all the investors interpret in the same way the relevant information divulged in the market, what can be explained by the following divergent or different conditions: beliefs, values, quality of the database that they use, level of technical knowledge and importance they attach to the qualitative and quantitative information extracted from the object of evaluation. The research aims to understand the logic of the process of financial decision-making of part of the individual segment in Brazil. Therefore, an inquiry of heuristics and the biases present in the decision making of those people, considering that the investor and the consumer are influenced by various factors. A research based on basic fundamentals of behavioral finance was applied in a demographically qualified sample of subscribers of one of the main Brazilian publishing companies. Of this total, we have obtained response from 641 Brazilians segmented by gender, age, income and education. In the research, the presence of heuristics and biases was evaluated in each group, such as overconfidence, representativeness, anchorage and procrastination. The results showed that both reason and emotion influence the participants’ answers of the bulk of the sample. Most people felt that their financial behavior is more rational than that of their peers. As expected, the study indicated significant differences in behavior according to gender, age, education and income. Key words: Behavioral finance. Efficient market. Risk. Return.